Modelo de dano concentrado aplicado à flambagem local em perfis vazados de aço estrutural submetidos à flexão composta - Silva, Leonardo Andrade Bispo (2020)
The quest to reduce engineering costs leads to the development of new materials and design concepts that seek lighter and more daring structures. In this way, the great advances in the manufacturing processes lead to the more frequent use of metal profiles with reduced thicknesses and high yield stress. Therefore, the use of structural parts with transverse sections composed of thin plates turn the phenomenon of local instability more evident and it is usually treat as a form of collapse. Since the mathematical modeling of the structure's behavior in relation to local buckling requires laborious and refined solutions, the finite element method is use in its classical formulation using meshes with several elements, resulting in an increase in computational cost. On the other hand, a recent nonlinear theory called Lumped Damage Mechanics (LDM) was introduced to obtain more realistic and efficient results in the analysis of more complex structures. In LDM theory, it is assumed that all the nonlinear effects of a finite element are concentrated on plastic hinges, which significantly reduces the computational cost of the analysis. As a result, the present work seeks to develop numerical models, using LDM, applied to local buckling in hollow section profiles subjected to bending and axial forces. In the model formulation it is necessary to insert values of some experimentally obtained parameters, such as the critical plastic rotation and the slope of the damage evolution line. In this work two numerical models were proposed, with equations based on Yamada et al. (1993, 2012) and AISC (2016), to analytically calculate those parameters and the last moment. To evaluate the accuracy of the models, the numerical results were compared with six experiments by Kazuya (2017), in which rectangular hollow section columns were submitted to axial compression force and a monotonic bending moment loading. Analyzing the results it is possible to conclude that the results of the model based on Yamada et al. (1993, 2012) were satisfactory, while the model based on AISC (2016) had conservative last moments when compared to the experimental ones.